Phosphorus and Silicon Uptake By Corn (Zea mays L.) in Response to Silicon Application in Calcareous Soil - Al-Rubie, Jumana A. Jawad; A. Abdulkareem , Mohammed (Nabatia, 2024)
A field experiment was conducted on clay soil at the Agricultural Research Station, College of Agriculture, University of Basra, Basra, Iraq, to investigate the impact of silicon addition on phosphorus and silicon uptake in corn plants. Silicon was applied as potassium silicate (26.5% Si2O) at 0 and 200 kg Si ha^-1 in two doses: on planting day and two weeks after planting. Phosphorus was applied as concentrated superphosphate or diammonium phosphate at 0, 12.5, 25, and 50 kg P ha^-1 on planting day. Measurements included soil available phosphorus at two stages, leaf phosphorus and silicon concentrations at two stages, grain phosphorus concentration, and the uptake and ratio of the two elements. Results showed that adding silicon increased soil available phosphorus, leading to higher phosphorus and silicon concentrations in leaves and improved uptake of both elements, along with increased grain phosphorus concentration. The Si/P uptake ratio also rose with silicon addition. Higher phosphorus levels boosted soil available phosphorus, enhancing phosphorus and silicon concentrations and uptake, and increased grain phosphorus concentration. The Si/P ratio decreased with rising phosphorus levels. Diammonium phosphate outperformed concentrated superphosphate in all uptake parameters. The study concludes that applying silicon at 200 kg Si ha^-1 can enhance phosphorus and silicon absorption. The Si/P ratio demonstrated that silicon uptake was significantly higher than phosphorus uptake, by nearly four times in some parameters. It is recommended to use silicon to treat corn plants under stress, as the plant accumulates a high amount of silicon, qualifying it as an accumulative species.